Adolescent Spinal Pain-Related Absenteeism as an Antecedent for Early Adulthood Work Presenteeism. - Beales, Darren; Coenen, Pieter; Smith, Anne; Harris, Mark; Pransky, Glenn; OʼSullivan, Peter; Straker, Leon (2020)
OBJECTIVES: This study investigated spinal pain-related absenteeism at age 17 as a potential precursor to work presenteeism at age 23.